Über grosse Abweichungen von Summen der Zufallsgrößen mit der Zahl von zufälligen Summanden - Aksomaitis, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Аксомайтис. О больших уклонениях сумм случайного числа случайных величинA. Aksomaitis. Apie didelius atsilenkimus atsitiktinių dydžių sumoms su atsitiktinių dėmenų skaičiumi